A methods engineering study on San Buena Garments - Gamboa, Gabriella R.; Lanante, Rinacina Tatiana L.; Tamayo, Merryl Antoinette B. (Diliman, Quezon City College of Engineering, 2003)
San Buena Garments is involved in the production of denim jeans of various styles, a business that requires high standard of quality due to elevated demands in the present market. The production starts with Coding, the marking of all cut goods. The second process is the Preparation, which involves the completion of the front and back sections of the garment. The next operation is Revising in which the completed panels are inspected for defects. Then, the non-defective panels undergo pairing. The Assembly of the pants is composed of nine basic operations. The last operation is Final Revising in which the quality control inspects the finished product. Like any other manufacturing companies, San Buena Garments encounters problems in their main production initiated by their current methods of manufacture. Using the Streamline Diagnosis Diagram, the following main production problems have been identified : a) frequent machine breakdowns; b) lack of daily production planning per operation; c) inadequate ventilation; d) insufficient lighting; e) poor housekeeping; f) ineffective hiring system; and g) ineffective training system. The group generated solutions for each problem through cost benefit analysis and value engineering. In order to solve frequent machine breakdowns, a recording system must be followed to generate proper allocation of repair expenses and effective preventive maintenance. Time study must be utilized to determine the processing times of each operation and set the daily quota of output per worker. Installation of four wall fans in the production area is the proposed solution for inadequate ventilation. Replacement of the 9 defective fluorescent lights must be considered to improve the lighting condition of the work area. Moreover, poor housekeeping can be resolved by implementation of a proposed cleaning schedule to be executed by the bundle boys. An improved hiring and training system must be implemented to be able to solve the problem on unskilled workers. Furthermore, an implementation plan and strategy is proposed to ensure effectivity of the stated solutions. Having solved the above problems will significantly reduce production delays of the company.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: San Buena Garments; Clothing trade; Systems analysis